Electrochemistry of carbon dioxide corrosion mitigation using tall oil diethylenetriamine imidazoline as corrosion inhibitor for mild steel. Issue 7 (29th October 2015) - Jevremović, I.; Singer, M.; Nešić, S.; Mišković‐Stanković, V.
Abstract : The inhibition effect of tall oil diethylenetriamine imidazoline (TOFA/DETA imidazoline) on corrosion of mild steel in CO2 ‐saturated 3 wt% NaCl solution was investigated by electrochemical impedance spectroscopy (EIS), potentiodynamic sweep (PDS), cyclic voltammetry (CV), quartz crystal microbalance measurements (QCM), and scanning electron microscopy (SEM). TOFA/DETA imidazoline is a mixed‐type corrosion inhibitor with the predominant anodic effect. The results of CV measurements indicate inhibited electrode processes in the presence of TOFA/DETA imidazoline and the absence of the rapid degradation of TOFA/DETA imidazoline in the range of mild steel corrosion potential. The corrosion rate of mild steel significantly decreased in the presence of TOFA/DETA imidazoline, while the inhibition efficiency increased up to 92%. It was found that the adsorption of studied imidazoline compound on steel surface followed both Langmuir and Temkin adsorption isotherms. The value of molecular interaction constant calculated from Temkin adsorption isotherm implied the existence of lateral repulsion between adsorbed inhibitor molecules.